Day two post retrieval 1500 IUI hCG bolus, progesterone-free luteal support post GnRH agonist trigger – a proof of concept study. (1st February 2018) - Vanetik, Sharon; Segal, Linoy; Breizman, Tatiana; Kol, Shahar
Abstract: Small dose of hCG (1500 IU) on the day of oocyte retrieval, followed by daily progesterone administration, is currently the preferred way to secure adequate luteal support following GnRH agonist trigger. In the current proof-of-concept study, we explored the possibility that a bolus of 1500 IU hCG, given two days after oocyte retrieval, may be sufficient to sustain adequate luteal support without additional progesterone treatment. From February 2015 to August 2016, we obtained 44 pregnancies following GnRHa trigger followed by day 2 hCG (1500 IU) support only (study group). Data from these 44 cycles were compared with the latest 44 pregnancies obtained following hCG (6500 IU) trigger followed by conventional progesterone luteal documented (control group). Mean progesterone levels (14 days postoocyte retrieval) in the study and control groups were 197 nmol/l and 173 nmol/l, respectively (NS). Mean E 2 levels (14 days post oocyte retrieval) in the study group was 6937 pmol/l, significantly higher ( p  < .001) than in the control group (3.276 pmol/l). We conclude that bolus of 1500 IU hCG, administered 2 days after retrieval, can provide excellent support, without the need to further supplement with progesterone.